THE INFLUENCE OF SELF-EFFICACY, KNOWLEDGE SHARING, AND LOYALTY BEHAVIOR ON THE PERFORMANCE OF STATE CIVIL EMPLOYEES IN THE PROVINCIAL SECRETARIAT OF NORTH SUMATRA WITH JOB SATISFACTION AS AN INTERVERNING VARIABLE - Dewi Safariani; Prihatin Lumbanraja; Elisabeth Siahaan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The development of modern government organizations is influenced by its administration and management system, which consists of three main components: constitution, law, ethics, departments, and council. The success of an organization depends on the human resources department, which includes employees, managers, and the quality and quantity of work performed by employees. Every organization aims to improve the performance of its employees in order to achieve organizational goals. Factors that influence employee performance include the ability to achieve targets, employee effectiveness, organizational effectiveness, employee effectiveness, employee work quality, employee knowledge quality, organizational focus on employee loyalty, and the level of employee involvement in the organization. Organizations also focus on employee loyalty, that is, individual contributions to the success of the organization. Organizational success depends on a variety of factors, including employee performance, knowledge, and loyalty. This research uses quantitative research. This research was conducted at the State Civil Apparatus at the Regional Secretariat of North Sumatra Province at the Goods and Services Procurement Bureau of the Regional Secretariat of North Sumatra Province. This research was conducted from April 2022 to October 2023.